PENGARUH STRESS KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA, TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. TRIMITRA SENTOSA INDONESIA BOGOR - Sadikin, Mochamad Rizki (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study was to determine the effect of work stress, work discipline and work environment on work productivity at PT. Trimitra Sentosa. The object of this research is all employees who work at PT. Trimitra Sentosa. This research was conducted on 44 respondents using a quantitative descriptive approach. Determining the sample size using a saturated sample technique that is taking the entire population. The approach used in this study is the Structural Equation Model (SEM) with the Smart-PLS analysis tool. Thereforethe results of this study state that the variable work stress has a significant positive effe ct on work productivity, work discipline has a significant positive effect on work productivity and work environment has a significant positive effect on work productivity at PT. Trimitra Sentosa Indonesia Bogor